2017
DOI: 10.1016/j.celrep.2017.12.001
|View full text |Cite|
|
Sign up to set email alerts
|

Allele-Specific DNA Methylation and Its Interplay with Repressive Histone Marks at Promoter-Mutant TERT Genes

Abstract: SUMMARY A mutation in the promoter of the Telomerase Reverse Transcriptase (TERT) gene is the most frequent noncoding mutation in cancer. The mutation drives unusual monoallelic expression of TERT, allowing immortalization. Here we find that DNA methylation of the TERT CpG Island (CGI) is also allele-specific in multiple cancers. The expressed allele is hypomethylated, which is opposite to cancers without TERT promoter mutations. The continued presence of Polycomb repressive complex 2 (PRC2) on the inactive al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
131
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(152 citation statements)
references
References 41 publications
13
131
1
Order By: Relevance
“…Several studies have identified an association between PRC2 activity, H3K27me3 enrichment, and DNA hypermethylation in tumors [28,30,[35][36][37][38][39]. To investigate the increased DNA methylation in our selected target genes (IRX2, NKX6-1, FOXE1, CABYR, and NRG1), we analyzed H3K4me3 and H3K27me3 enrichment in their promoter regions using ChIp.…”
Section: H3k4me3 H3k27me3 and H3k4me0 Enrichments At Selected Targementioning
confidence: 99%
“…Several studies have identified an association between PRC2 activity, H3K27me3 enrichment, and DNA hypermethylation in tumors [28,30,[35][36][37][38][39]. To investigate the increased DNA methylation in our selected target genes (IRX2, NKX6-1, FOXE1, CABYR, and NRG1), we analyzed H3K4me3 and H3K27me3 enrichment in their promoter regions using ChIp.…”
Section: H3k4me3 H3k27me3 and H3k4me0 Enrichments At Selected Targementioning
confidence: 99%
“…Furthermore, cells that are heterozygous for TERT promoter mutations exhibit allele‐specific characteristics. As an example, the mutant promoter exhibits activating H3K4me2/3 chromatin marks and low CpG methylation upstream of the TSS, while the wild type promoter is epigenetically silenced by the H3K27me3 mark and has dense CpG methylation . In urothelial cancer cell lines, TERT has monoallelic expression, with expression occurring only from the mutant allele …”
Section: Introductionmentioning
confidence: 99%
“…As an example, the mutant promoter exhibits activating H3K4me2/3 chromatin marks and low CpG methylation upstream of the TSS, while the wild type promoter is epigenetically silenced by the H3K27me3 mark and has dense CpG methylation. 23 In urothelial cancer cell lines, TERT has monoallelic expression, with expression occurring only from the mutant allele. 24 TERT expression and telomerase activity are present in thyroid cancer but absent in normal thyroid cells.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated THOR region where methylation of CpG sites is generally associated with increased TERT expression 16,36 . However, our data show that increased TERT expression in BCC tumors can be primarily attributed to the promoter mutations as shown in adult gliomas 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The mutations within the TERT promoter create de novo binding sites for ETS transcription factors that lead to increased transcription through massive epigenetic histone modification 14,15 . Methylation within TERT hypermethylated oncological region (THOR) also reportedly de-represses the TERT transcription 16 . Besides TERT promoter, other frequent noncoding mutations in BCC include those involving a bidirectional DPH3 promoter 17 .…”
Section: Introductionmentioning
confidence: 99%